New ‘oligopseudocellar’ Protaphorura species (Collembola: Onychiuridae) from East Palaearctic - Mikhail Potapov; Ayuna Gulgenova (Soil Organisms, 2024)
Four new species of the genus Protaphorura (P. dorzhievi sp. n., P. buryatica sp. n., P. dzherga sp. n., and P. uniparis sp. n.) with reduced number (0–1–2) of pseudocelli on the thoracic tergites are described from Buryatia (Russia, East Siberia). P. jacuticaMartynova, 1976 is redescribed based on type and newly collected material. The key to Asiatic species with pseudocellar formula 0–1–2 on thorax is given.